LIVER CIRRHOSIS - STATISTICAL ANALYSIS DATA IN A 5 YEAR PERIOD IN PRILEP, REPUBLIC OF NORTH MACEDONIA - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2020)
Liver cirrhosis is defined as a diffuse process, which is characterized by fibrosis and the conversion of normal liver architecture to abnormal nodules. For the purposes of this paper was used data from the Institute for Public Health in Prilep, Republic of North Macedonia in the period of 2014 to 2018. The data were analyzed and processed epidemiologically, descriptively and statistically. The total number of hospitalized patients in the analyzed period is 107 patients. The highest number of cases was registered in 2015 with 31 patients ie 29% and the lowest number in 2018 with 9 patients or 8%. According to gender, cirrhosis affected men more - 79 patients (74%) than women - 28 patients (26%). According to the age structure, the most of the cases were from 55 to 64 years old – 55 patients (51%). According to the etiological distribution, alcohol is the main cause of cirrhosis in Prilep region - 59 cases (55%). According to the hospitalization ie the number of hospital days, over a period of 5 years the number of hospital days is 432. In other patients the exact cause of cirrhosis has not been established. Analysis shows that the risk and severity of liver complications endanger life and quality of life and increase morbidity and mortality.